Management Style and Employee Engagement in Blue Collar Workers - Moodley, Sheila (University of the Witwatersrand, Johannesburg, 2021)
A noteworthy and important part of South Africa is that “blue collar workers make up the backbone of the country’s economy” and as such, it is important to pay attention to the work related well-being of these workers in order to become a more productive nation with a more satisfied workforce (Brand-Labuschagne, Mostert, Rothmann and Rothmann, 2012:6). In the State of Labour Report (2016) it is recorded that 3 out of every 4 people in the South African working population are blue collar workers. Thompson (2001) found that the blue collar environment is dominated by black South Africans and argued that it is worthwhile to attempt to identify the perceptions and behaviours of black South Africans in the blue collar environment to address the challenges facing South Africa. In the field of employee engagement it has been found that engaged employees “show higher job and organisational performance, positive job attitudes, higher psychological well-being and proactive job behavior” (Makikangas, Schaufelli, Tolvanen and Feldt, 2013: 136). It has further been established that employee engagement is directly linked to a number of positive organisational outcomes that include improved productivity, increased job satisfaction, higher levels of motivation, employee commitment, reduced turnover intention, increased customer satisfaction, better returns on assets, profits and shareholder value (Bakker, Demerouti and Schaufeli, 2003; Bakker, Schaufeli, Leiter and Taris, 2008; Harter, Schmidt and Hayes, 2002; Schaufeli and Bakker, 2004; Lee and Mohammed, 2006; Brand- Labuschagne, Mostert, Rothmann and Rothmann, 2012). The State of Employee Engagement Report (2019), found that leaders and immediate supervisors make the biggest difference in employee engagement and the research of Kahn (1990) points to engaging the mind, body and soul of the person in the performance of their work as a way of improving employee performance
A research report submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2021
Keywords: Employee Engagement; Blue Collar Workers; Management style; Economy; UCTD; SDG-8: Decent work and economic growth